Learning obstacle on the material circumference and area of triangle in Limpung junior high school number 2 - Muhammad Prayito (International Journal of Science and Applied Science: Conference Series, 2017)
The purpose of this research was to analyze the characteristics of learning obstacle contained in the concept of circumference and area of a triangle in SMP N 2 Limpung. Data about learning obstacle Obtained through analysis of the results of the students' answers to the test and learning processes within the material circumference and area of triangles. This study is a qualitative study using of didactical design research method. The research result in learning identified material of circumference and area of a triangle were didactical, ontogenic and epistemological obstacle. As for learning obstacle found are: (1) distinguishing concept image material high line, bisecting line, line weight and line axis; (2) determine the high line on the triangular side of the base is not horizontal; (3) Determine the triangle area an obtuse triangle; and (4) visualization of the students regarding the ability to determine the type of triangle and the position of the perpendicular line or field.